Contexts for teacher practice: (Re)Considering the role of context in interventions in early childhood teacher engagement with new approaches to shared book reading - Katherine K. Delaney; Susan B. Neuman (Arizona State University, 2016)
Although the randomized controlled trial has been regarded as the sine qua non in recent years, we argue that understanding contexts for teacher practice is a critical factor in the implementation of intervention, but has often been overlooked in educational research design. In this paper, we argue that randomized trials may not be ideal for educational contexts that are multi-faceted, complex and often part of other community-based initiatives. To make this argument, we describe a study from "the context out," a different lens than is typical in education research. In doing so, we consider how varied contexts create both constraints and affordances for teachers to engage in an intervention. Examining how teachers engage with new curricular practices, we focus closely on five early childhood centers in high poverty neighborhoods, using mixed methods to understand both the influence of the intervention as well as the conditions that either supported or thwarted changes in practice. Our findings suggest that context plays a major role in educational practice, which has important implications for approaches to research in the future. Given this reality, we argue that an understanding of the context in which an intervention takes place must be considered in any calculation of "what works" in classrooms.